Social Representations of Breast Cancer in Patients, Accompanying Relatives and Specialists - Maria Elena Reina Suarez; Yamila Ramos Rangel; María de los Ángeles Reina Sarmiento; Leonor Cisneros Pimentel; María del Rosario Lleó Moreno; Sara Soraya Naranjo Noda (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Background: unveiling the social representations of breast cancer can bring professionals in the psychological sciences to understand attitudes, behaviors and the influences they exert on patients, family members and specialists. Objective: to determine the structure of the social representations (attitude, information, representational field) of breast cancer in the study subjects. Methods: exploratory, cross-sectional study, of mixed methodology, in the period from May 2014 to December 2015. Applied as techniques: sociodemographic and clinical data form, semi-structured interview, composition, free association. The variables analyzed were: addressability of the attitude towards the diagnosis of breast cancer, addressability of the attitude towards treatments, in the information dimension: knowledge about disease conceptualization, knowledge of symptoms, knowledge about treatments, beliefs about risk factors , opinions on the consequences of breast cancer, opinions on the need to provide knowledge of the disease to patients, relatives. Descriptive statistical analysis of frequencies was performed. The information of the variables in the database of the statistical package SPSS 15.0 for Windows was processed. The results were expressed in absolute and relative frequencies. Results: patients, relatives showed addressability of the negative attitude towards diagnosis and treatment. There was a prevalence of adjusted responses in the explored areas of the information dimension, although with a homogeneous level of depth, in family members. The representative field of breast cancer accounted for mostly models of disease challenge in the study subjects. Conclusions: the subjects of the study in relation to breast cancer showed a negative attitude, there was a predominance of adjusted answers about the pathology information and mostly models of disease challenges.